Legal Responsibility of Notaries for Errors and Misuse in the Use of Electronic Certificates as Evidence in the Digital Era - Rere, Laode Reyhan Muhammad Fitra; Disaely, Rico Marleve; Samosir, Tetti (JURNAL AKTA, 2025)
The development of information technology has driven modernization in various legal fields, including notarial services. One form of innovation is the use of electronic certificates in making notarial deeds. This study aims to analyze the form of legal responsibility of notaries for errors and misuse in the use of electronic certificates and to assess the adequacy of regulations governing their legal protection. The method used is normative legal research with a statutory regulatory approach and legal literature analysis. The results of the study indicate that notaries can be held accountable civilly, criminally, or administratively if there is a violation in the use of electronic certificates. Although the use of electronic certificates has a legal basis through the ITE Law and its implementing regulations, existing regulations do not fully regulate in detail the technical mechanisms, responsibilities, and supervision of notaries in the digital context. Therefore, it is necessary to prepare more technical and specific regulations to ensure legal certainty and protection for parties who use notary services in the digital era.